Ethnicity and Home Ownership in Montreal, 1921–51 - Choko, Marc (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1998)
Montreal has long been perceived as “a city of tenants” in a North-American world of owners. This perception has been explained by the strong presence of French Canadians who were poor and had a lower preference for home ownership.This article provides for the first time relevant data that allows a detailed comparison of housing types, values, tenure and occupations of French Canadians, English Canadians and immigrants from Southern and Eastern Europe, and for the cities of Montreal, Lachine, Outremont, Verdun and Westmount, between 1921 and 1951.Indeed, Montreal was largely a town of tenants living in plexes. But these data show that, in proportion, French Canadians were as much owner-occupants as other ethnic groups and that, in fact, the low rate of owner-occupancy was due more to English Canadians and Eastern Europeans who were attracted to the new apartment buildings.These data also show that one can be a wealthy tenant living in a downtown apartment of great value, or the owner with limited means of a house of little value on the outskirts of the city.